PROMOTING GREEN BEHAVIOR AT WORKPLACE: A LITERATURE REVIEW - Masliza Binti Mohd Razali; Nur Muhammad bin Sam; Abdul Hanif bin Roslan; Faizzul Hakim bin Ahmad Jeffy; Muhammad Faqih Shaib bin Norazam (International Journal of Accounting, Finance and Business, 2022)
The increasing environmental issue is being debatable around the globe.Sustainability of the environment is an aim that many companies have included in theirobjectives. Employee Green Behavior (EGB) is environmentally friendly practice in theworkplace that serves as a foundation in achieving sustainable development plan into action.This paper aims at presenting the reviews of the literature on EGB trends and its importance.A literature search in different scientific databases was employed to identify studies thatexamine green behavior, mainly from 2017 to 2021. The review will give a holisticunderstanding of the concept of green behavior for future researchers and aid to identify theresearch gap.